APA KABAR PEMBAHARUAN PEMIKIRAN ISLAM? (Meneropong Pembaharuan Pemikiran Islam Post Cak Nur - Gus Dur) - Moch Iqbal (IAIN Bengkulu, 2019)
In the 1990s the world of Islamic thought was very crowded and dynamic. There are some Islamic thinkers of the country who are very interested in producing discourses on Islamic thought. Some of them were (alm) Nurcholis Madjid and (alm) Abdurrahman Wahid (Gus Dur). Although the political realm of the homeland at that time began to warm up, the Islamic thought movement was very dynamic. After the fall of the new Order in 1998, and the death of several Islamic thinkers, the Islamic thought movement seemed to experience congestion. Even now it is quiet from healthy Islamic thinking. All components of thought are absorbed in the ups and downs of the political stage which attracts much attention. the results of this paper show that the political stage turned out to be more attractive to the generation of Islamic intellectuals post Cak Nur - Gus Dur.